2023
DOI: 10.3390/environments10020030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Solids Accumulation on Greenhouse Gas Emissions, Substrate, Plant Growth and Performance of a Mediterranean Horizontal Flow Treatment Wetland

Abstract: In treatment wetlands (TWs), solids accumulation can result in hydraulic malfunction, reducing the operation life, and it could enhance biological activity by favoring biofilm development. It is still unknown whether the solids accumulation can affect greenhouse gas (GHG) emissions. This study aims to evaluate the solid concentration along a horizontal flow (HF) TW, and its role in GHG emissions, hydraulics, treatment performance, and vegetation development (Phragmites australis (Cav.) Trin. ex Steud.). The st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…Our results showed that, in the partially clogged areas of the HSTW, there was a lower culms number with higher dry weight per culm and height, while in the unclogged areas, the number of culms was higher, but each plant had a lower dry weight and height. In addition, the higher weight of each plant in the partially clogged area, with respect to the unclogged zone, coincided with higher fiber fractions and DM contents, due to a large quantity of organic matter and solids in the inlet of the HSTW unit, as also supported by the findings of [40] in terms of the lower COD removal efficiency observed in T1. All of this is also confirmed by the biomethane yield results obtained from the BMP assays.…”
Section: Discussionsupporting
confidence: 54%
“…Our results showed that, in the partially clogged areas of the HSTW, there was a lower culms number with higher dry weight per culm and height, while in the unclogged areas, the number of culms was higher, but each plant had a lower dry weight and height. In addition, the higher weight of each plant in the partially clogged area, with respect to the unclogged zone, coincided with higher fiber fractions and DM contents, due to a large quantity of organic matter and solids in the inlet of the HSTW unit, as also supported by the findings of [40] in terms of the lower COD removal efficiency observed in T1. All of this is also confirmed by the biomethane yield results obtained from the BMP assays.…”
Section: Discussionsupporting
confidence: 54%